The Influence of Motivation and Incentives on Employee Performance at the Luwu Regency Inspectorate Office - Uliyah, Nur; Sukri, Sukri; Dirham, Dirham (International Journal of Management Science and Information Technology, 2024)
This research aims to determine the effect of motivation and incentives on employee performance. This type of research is quantitative research. The data collection method for this research uses a questionnaire addressed to all employees of the Luwu Regency Inspectorate. The sampling technique used is saturated sampling where the entire population is sampled. The sample used for this research was 160 people. The analytical methods used are validity, reliability, and multiple regression tests. The research results show that: 1) motivation has a positive and significant effect on the performance of Luwu Regency Inspectorate employees, and 2) incentives have a positive and significant effect on the performance of Luwu Regency Inspectorate employees.